Assessment, pharmacological therapy and rehabilitation management of musculoskeletal pain in children with mucopolysaccharidoses: a scoping review - R. Gnasso; B. Corrado; I. Iommazzo; F. Migliore; G. Magliulo; B. Giardulli; C. Ruosi (Orphanet Journal of Rare Diseases, 2022)
Abstract Background Pain of musculoskeletal origin is very common in young patients affected by Mucopolysaccharidoses. This scoping review evaluates the evidence for assessment, pharmacological treatment and rehabilitation management for musculoskeletal pain of the latter. Methods A Medline search through PubMed has been performed for studies published in English at least for the past twenty years. Two investigators independently reviewed all search results and extracted those that met the inclusion criteria. Results 29 studies have been selected and analysed in depth, of which 10 related to pain assessment, 11 concerned pharmacological approach, and 8 reported rehabilitation approaches. Conclusion Few data are available in literature concerning the classification and management of pain in children with Mucopolysaccharidoses. Notwithstanding, pain evaluation methods are effectively used to classify pain intensity, according to the age group and communication abilities of young Mucopolysaccharidoses patients. The review emphasizes that drug therapies have a palliative purpose, while rehabilitation reduces musculoskeletal pain and can provide a therapeutic effect on disabilities.